Urinary and Faecal Incontinence Among Adults with Stroke in South-West Nigeria – A Cross Sectional Survey - Desmond, Zaki A.; Mahmud, Karaga A.; Joana, Adeleke O.; Omotayo, Tabiti O.; Lateefat, Lawal B.; David, Farounbi A.; Abubakar, Saleh B. (Darul Yasin Al Sys, 2025)
Background: Urinary incontinence (UI) post-stroke has been identified as major problem among stroke survivors. The aftermath of faecal incontinence (FI) is always disturbing as it may lead to low self-esteem, caregiver stress and reduced rehabilitation participation. There is dearth of publication on urinary and faecal incontinence among adults with stroke in Nigeria.Aim: This study was designed to determine the prevalence as well as the association between UI and FI among adults with stroke in South-West Nigeria. Methods: Fifty-three participants were enlisted by consecutive sampling technique for this cross-sectional study. The Wexner/Cleveland Clinic Florida Incontinence score (CCFIS) and International Consultation on Incontinence Questionnaire Short Form (ICIQ-UI SF) were administered for data collection. Descriptive statistics of mean, standard deviation, percentages and frequency were used to summarize obtained data, inferential statistics of Chi-square was used to determine the association between UI and FI, and between gender and UI and FI among the participants. Also, Spearman’s correlation was used to assess the relationship between age and duration of stroke and each of UI and FI. Alpha was set at 0.05. Results: The mean age of the participants was 52.98±14.564 ranging from 24 to 80 years. The prevalence of UI was 69.8% while FI was 47.2% and there was no significant association between them. However, there was significant relationship between FI and duration of stoke. On the other hand, there was no significant relationship between UI and duration of stroke, but there was significant relationship between Age and FI and UI. Conclusion: The occurrence of UI and FI are independent of each other, patient age is associated with a risk of developing both UI and FI post stroke, while gender is not strong a determinant of post stroke UI and FI. Additionally, duration of stroke could significantly influence FI but not UI post stroke. More research on aetiology, incidence, and possible prevention and management of UI and FI post stroke is recommended.